Hubungan Antara Modal Usaha, Jam Kerja, Lama Usaha Terhadap Pendapatan Pedagang Tahu di Kecamatan Tabanan - Permadi, I Komang Oka; Agustina, Ida Ayu Sintha; Ayuk, Ni Made Taman (Universitas Tabanan, 2024)
This study attempts to ascertain the impact of business capital, working hours, and duration of operation on the revenue of tofu sellers in Tabanan sub-district, Tabanan regency. With a population of 213 business units of tofu traders in Tabanan sub-district, Tabanan district, the focus of this research object is business capital, working hours, and length of business on the income of tofu traders. A sample of 68 business units of tofu traders was obtained using the probability sampling method and slovin formula.According to the test results, working hours, business capital, and business length all have positive and significant effects on tofu dealers' income in Tabanan sub-district, Tabanan regency.